Effect of Aluminium and Copper Powder Addition in Alumina Matrix on Bending Strength - Hendriwan Fahmi; Yanto, Asmara; Sulaeman (Jurnal Teknik Mesin, 2016)
The aim of this research is to find out the influence of the addition of aluminum (Al) and copper (Cu) on matrik alumina (Al2O3) against the forces of bending. Of aluminum made by a process of water and atomization of copper made by the process of atomization centrifugal. Consisting of copper aluminum and continued with a sifting using a measure of 50 - 100 mesh up to get the size of the amounting to 150 - 125 µm. of the measures followed by the process of mixing with the variation of a composition of 100 % of the volume of Al2O3, 90 % of the volume of Al2O3 + 10 % heavy Al and Cu, 80 % of the volume of Al2O3 + 20 % heavy Al and Cu, 70 % of the volume of Al2O3 + 30 % heavy Al and Cu, al2o3 + 60 % of the volume of 40 % heavy Al and Cu. Then will be the process of compacting with pressure 140 MPa. The process of sintering committed using furnace with the temperature 1050 OC by heating rate 5 OC / minute. In this research voltage power bending highest obtained in composition 80 % of the volume of Al2O3 + 20 % heavy Al and Cu to voltage bending average of 6,66MPa.